Cognitive problems in multiple sclerosis: a mixed methods study on the perceived effectiveness and service provision of cognitive rehabilitation - Klein, Olga (2019)
Introduction: Up to 70% of people with multiple sclerosis (MS) experience mild to moderate cognitive deficits in attention, memory, information processing speed, and executive functioning. Cognitive rehabilitation to address such deficits has emerged as a potential treatment approach, but the evidence regarding its effectiveness is mixed. It is also unclear how cognitive rehabilitation is currently delivered in the UK.